(Re)investigation of Rural Women's Labour Supply in India: The Impact of Household Poverty Status—A Panel Data Analysis. (November 2019) - Sebastian, Nancy
This article examines the role of household poverty in shaping rural female labour supply using the unique panel dataset of India Human Development Survey. The results using Vella and Verbeek's two-step panel estimation reveal the presence of a backward-sloping labour supply curve for rural women from below poverty line households, and an upward-sloping labour supply for rural women from above poverty line (APL) households. This implies the existence of 'forced' or 'need-based' participation among poor women and justifies why they work long hours in poorly paid hazardous jobs. The article also finds horizontal labour supply among agriculture wage workers and for Adivasi and Dalit rural women to some extent, reflecting limited job options, and surplus unskilled labour who are unable to demand higher wages for their labour supply. On the other hand, when categorised by occupation type, the downward-sloping labour supply for rural women from APL households indicates the dominance of the income effect over the substitution effect, and the socio-cultural factors that gain strength as income levels increase. JEL Classification: J220, R21, J16, R230, I32